2011
DOI: 10.1242/jcs.080465
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Fbxo7 reveals its regulatory role in proliferation and differentiation of haematopoietic precursor cells

Abstract: Research Article 2175 IntroductionDuring the cell cycle, ubiquitin-mediated proteolysis provides a swift and precise means to regulate the abundance of cell cycle regulatory proteins, including cyclins and cyclin-dependent kinase (Cdk) inhibitors. This mechanism for regulating the turnover of proteins is mediated through ubiquitin ligases, which transfer ubiquitin to target proteins, enabling their timely destruction (Hershko, 1997;Hershko and Ciechanover, 1998;Nakayama and Nakayama, 2006;Reed, 2006;Reed, 2003… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…Fbxo7 expression was reduced using a previously validated shRNA construct [9]; cells were differentiated by DMSO treatment; and haemoglobin concentration was measured over time (Figure 3A). Control cells accumulated haemoglobin over 5 days, whereas cells expressing Fbxo7 shRNA (Fbxo7-sh) did not, demonstrating a requirement for Fbxo7 in MEL differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fbxo7 expression was reduced using a previously validated shRNA construct [9]; cells were differentiated by DMSO treatment; and haemoglobin concentration was measured over time (Figure 3A). Control cells accumulated haemoglobin over 5 days, whereas cells expressing Fbxo7 shRNA (Fbxo7-sh) did not, demonstrating a requirement for Fbxo7 in MEL differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…For IPs, 1 µg of anti-CDK2 or IgG, with 20 µl of Protein A/G agarose (Santa Cruz Biotechnology), or 20 µl of EZview anti-HA beads (Sigma) was used as previously described [9]. Beads were washed with kinase buffer (25 m m HEPES, pH 7.5; 5 m m MgCl 2 ; 2.5 m m MnCl 2 ; 0.5 m m DTT) prior to adding 0.75 µg of recombinant 6 × His-Rb (amino acids 792–928; ProSpec, Ness-Ziona, Israel), 37.5 µ m ATP, and 1 μCi of [γ- 33 P]ATP for 30 min at 30 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the substrate degradation depends on its phosphorylation state (25), cell cycle, and intracellular localization (26). In addition, the functions of some FBPs are cell type-dependent (27)(28)(29). In an attempt to bypass these constraints and identify new SCF1(FBXO25) substrates, the ubiquitination in chip approach has been used.…”
Section: Discussionmentioning
confidence: 99%
“…Fbxo7 −/− mice show increased pro-B cell and pro-erythroblast populations 135 , but no information has been obtained regarding the role of FBXO7 in tumorigenesis. Biochemically, FBXO7 catalyses the ubiquitylation of hepatoma upregulated protein (HURP; also known as DAP5) 136 ; HURP is a putative oncogene, as its overexpression has been observed in human hepatocellular carcinoma, colon cancer, breast cancer and transitional cell carcinoma 136 .…”
Section: Undetermined But Probable Functions In Cancermentioning
confidence: 99%